Sinergi Maqasid Al-Syariah Dan Sustainable Development Goals (SDGs) Dalam Mewujudkan Pembangunan Berkelanjutan - Hamzah Zainuri; Muliadi; Ikhsan Fajri; Wahyuddin (Journal of Contemporary Indonesian Islam, 2026)
Sustainable development has become an increasingly important global agenda in addressing various contemporary challenges, such as poverty, social inequality, environmental degradation, and limited access to education and healthcare. The Sustainable Development Goals (SDGs) serve as a global development framework focused on human well-being and sustainability. Within the Islamic tradition, Maqasid al-Shari’ah places human welfare as the primary objective of Shari’ah through the protection of religion (hifz al-din), life (hifz al-nafs), reason (hifz al-‘aql), lineage (hifz al-nasl), and property (hifz al-mal). This study aims to analyse the conceptual relationship between Maqasid al-Shari’ah and the SDGs and to explain how the synergy between the two can support sustainable development. The study employs a qualitative approach using the library research method. Data were obtained from various relevant literature sources, including Scopus-indexed journal articles, accredited national journals, academic books, official SDG documents, as well as classical and contemporary works on Maqasid al-Sharia. Data analysis was conducted using content analysis techniques through a process of identification, classification, comparison and synthesis of the reviewed literature. The results indicate a strong alignment between the objectives of Maqasid al-Syariah and the SDG targets, particularly in the areas of health, education, poverty eradication, social equality and equitable governance. Islamic economic instruments such as zakat, waqf, sukuk, and Islamic social finance also hold great potential in supporting the achievement of various SDG goals. This study concludes that the synergy between Maqasid al-Syariah and the SDGs can serve as a more holistic development framework by integrating economic, social, environmental, moral, and spiritual dimensions to realise sustainable well-being.